Search for very high energy gamma-rays from the z = 0.896 quasar 4C +55.17 with the MAGIC telescopes. Issue 1 (11th March 2014) - Aleksić, J.; Ansoldi, S.; Antonelli, L. A.; Antoranz, P.; Babic, A.; Bangale, P.; de Almeida, U. Barres; Barrio, J. A.; González, J. Becerra; Bednarek, W.; Berger, K.; Bernardini, E.; et al.
Abstract: The bright gamma-ray quasar 4C +55.17 is a distant source ( z  = 0.896) with a hard spectrum at GeV energies as observed by the Large Area Telescope (LAT) on board the Fermi satellite. This source is identified as a good source candidate for very high energy (VHE; >30 GeV) gamma-rays. In general, VHE gamma-rays from distant sources provide a unique opportunity to study the extragalactic background light (EBL) and underlying astrophysics. The flux intensity of this source in the VHE range is investigated. Then, constraints on the EBL are derived from the attenuation of gamma-ray photons coming from the distant blazar. We searched for a gamma-ray signal from this object using the 35 h observations taken by the MAGIC (Major Atmospheric Gamma-ray Imaging Cherenkov) telescopes between 2010 November and 2011 January. No significant VHE gamma-ray signal was detected. We computed the upper limits of the integrated gamma-ray flux at the 95 per cent confidence level of 9.4 × 10 −12 and 2.5 × 10 −12  cm −2  s −1 above 100 and 200 GeV, respectively. The differential upper limits in four energy bins in the range from 80 to 500 GeV are also derived. The upper limits are consistent with the attenuation predicted by low-flux EBL models on the assumption of a simple power-law spectrum extrapolated from LAT data.